Categorical Determinations and Conceptual Notion of Education: Tensions between the Indo-European and Asian-Afro-Mediterranean Ethical Systems - Herra Castro, Ernesto (2018)
This paper identifies various educational moments that, as categorical determinations, have been subsumed and give meaning to the concrete notion, concept, of what education is. In this way the present concern tries to name the tensions that take place during the displacement of the centrality of the Indo-European ethical system, emerged since the XX century BC, by the Asian-Afro-Mediterranean ethical system, emerged since the fourth century AD. Given that these tensions are part of the pressure that we as a human species add to our common mother even today, we name such educational moments to promote other notions and/or educational possibilities more than those contained in the Modernity project to go beyond it.